2015
DOI: 10.1590/s1413-24782015206105
|View full text |Cite
|
Sign up to set email alerts
|

Mediações on-line em cursos de educação a distância os professores de língua portuguesa em questão

Abstract: O artigo discute os tipos de mediação on-line desenvolvidos em fóruns do curso "Práticas de Leitura e Escrita na Contemporaneidade" por assessores técnico-pedagógicos (ATP) e outros profissionais com formações distintas e de diferentes áreas e níveis de atuação da rede pública estadual de São Paulo. Partindo do pressuposto de que a formação universitária dos participantes levaria a uma performance otimizada por parte daqueles que tiveram uma formação básica em língua portuguesa, questiona-se se os professores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…[21] regarding the pedagogical mediation considers that it is not any activity, but it is a practice done with a purpose, it is not a simple interaction because it transforms, modifies and builds people. [14] in the study on online mediation in distance education courses they indicate that the teacher's role is to mediate Development Zone East in line with the thinking of Vygotsky, that is, encourage their development. MOOC around [20] in such a confluence of technological and pedagogical mediations is given, although they are explored in all its dimensions.…”
Section: Mediation In Open Environmentsmentioning
confidence: 85%
“…[21] regarding the pedagogical mediation considers that it is not any activity, but it is a practice done with a purpose, it is not a simple interaction because it transforms, modifies and builds people. [14] in the study on online mediation in distance education courses they indicate that the teacher's role is to mediate Development Zone East in line with the thinking of Vygotsky, that is, encourage their development. MOOC around [20] in such a confluence of technological and pedagogical mediations is given, although they are explored in all its dimensions.…”
Section: Mediation In Open Environmentsmentioning
confidence: 85%
“…A total of 94 articles were identified, eight of which were selected for systematic analysis, as they were in line with the present study (Balbé, 2003;Belloni, 2001;Hraste & Rodríguez, 2008;Moré, Moritz, Pereira, & Melo, 2010;Ozdemir & Abrevaya, 2007;Rangel, Costa, De-Angelis & Martins, 2015;Silva & Guimarães, 2011;Tarouco, Moro & Estabel, 2003). A rescue of the specific literature on LMS and on DE management, initially consulted, was also carried out, complementing it with studies identified in the theoretical review carried out at the end of the research, which totaled the consultation of more than twenty references on the subject.…”
Section: Grounded Theory Componentsmentioning
confidence: 87%
“…O avanço das tecnologias de informação e o crescente uso da internet possibilitaram o surgimento de um novo processo de comunicação (Assis, 2013;Rangel et al, 2015) e transformaram as estratégias de ensino e aprendizagem (Silva, Café e Catapan, 2010). Visando atender à demanda educativa, surgiu o movimento acesso aberto (open access, em inglês), que defende o acesso aberto à literatura e outros conteúdos de caráter acadêmico, científico ou técnico, sem restrições, online, livre de qualquer cobrança de taxa ou necessidade de assinatura, a qualquer pessoa, para que se possa ler, fazer download, copiar, distribuir, imprimir ou pesquisar (Müller, 2012).…”
Section: Introductionunclassified